Reindeer use of low Arctic tundra correlates with landscape structure - Skarin, Anna; Verdonen, Mariana; Kumpula, Timo; Macias-Fauria, Marc; Alam, Moudud; Kerby, Jeffrey; Forbes, Bruce C. (2020)
Rapid climate change in Arctic regions is linked to the expansion of woody taxa (shrubification), and an increase in biomass as tundra becomes greener. Reindeer and caribou (Rangifer tarandus) are considered able to suppress vegetative greening through grazing and trampling. Quantifying reindeer use of different land cover types can help us understand their impact on the growth and recruitment of deciduous shrubs, many of which serve as fodder (e.g. Salix spp.), in favourable habitats, such as naturally denuded landslides in permafrost areas. Understanding the spatial distribution of reindeer pressure on vegetation is important to project future patterns of greening, albedo, snow capture, active layer development, and the overall resilience of tundra rangelands under ongoing climate change. Here we quantify reindeer habitat use within the low Arctic tundra zone of Yamal, West Siberia estimated from pellet-group counts, and also how active layer thickness (ALT) relates to reindeer use. Our results confirm intensive use by reindeer of terrain with high June-July time integrated normalised difference vegetation index, steeper slopes, ridges, upper slopes and valleys, and a preference for low erect shrub tundra. These sites also seem to have a shallower ALT compared to sites less used by reindeer, although we did not find any direct relationship between ALT and reindeer use. Low use of tall Salix habitats indicated that reindeer are unlikely to suppress the growth of already tall-erect woody taxa, while they exert maximum pressure in areas where shrubs are already low in stature, e.g. ridgetops. Reindeer ability to suppress the regrowth and expansion of woody taxa in landslide areas (i.e. concavities) seems limited, as these types were less used. Our results suggest that reindeer use of the landscape and hence their effects on the landscape correlates with the landscape structure. Future research is needed to evaluate the role and efficiency of reindeer as ecosystem engineers capable of mediating the effects of ...